2010
DOI: 10.1166/jnn.2010.2410
|View full text |Cite
|
Sign up to set email alerts
|

Ferromagnetism Driven by Oxygen Vacancies in SnO<SUB>2</SUB> Nanowires

Abstract: Room temperature ferromagnetism has been observed in SnO2 nanowires synthesized by a chemical vapor deposition using Au layers as catalyst. The nanowires are homogeneous and single-crystalline grown along the [101] direction, with diameters ranging from 25 to 100 nm and length greater than 20 microm. The special magnetization reaches 0.114 emu/g for the nanowires with diameter of approximately 25 nm and reduces with increasing diameters. Branched SnO2 nanowires were prepared via a two-step vapor-liquid-solid a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 19 publications
1
39
0
1
Order By: Relevance
“…The ferromagnetic behaviors were more clearly observed in Fig.4(b) which show the hysteretic magnetization at 300 K. [6,7], are expected from these experimental results.…”
Section: Magnetic Propertiessupporting
confidence: 70%
See 2 more Smart Citations
“…The ferromagnetic behaviors were more clearly observed in Fig.4(b) which show the hysteretic magnetization at 300 K. [6,7], are expected from these experimental results.…”
Section: Magnetic Propertiessupporting
confidence: 70%
“…The ab initio calculations for the (TM) x Sn 1-x O 2 (TM= V, Mn, Fe and Co) were performed [1][2][3], and it was concluded that ferromagnetic moments appeared for Fe, Co, but not for V and Mn. In the study by our group [4], the TM oxides (V 2 O 5 , VO 2 Except for the TM-doped SnO 2 , the room temperature ferromagnetism, induced by the oxygen vacancies, has been reported for SnO 2 thin films, nano-particles and nano-wires [5][6][7][8]. As for the SnO 2 nano-particles [6], the sample preparations were performed by chemical reaction between organic solvent and metal nitrate.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 79 ] In addition, the atomic layer deposited process was applied to construct Pt–Ru dual‐metal dimers by successively depositing Pt and Ru atoms on N‐doped CNTs. [ 80 ]…”
Section: Polynary Metals Sacsmentioning
confidence: 99%
“…Therefore, many efforts have been devoted to develop highly efficient electrocatalysts to accelerate the OER kinetics and reduce the overpotential [8] . Although IrO 2 and RuO 2 are considered as the most efficient OER catalysts with outstanding kinetics and the lowest OER overpotential, the scarcity and high cost limit their applications in large‐scale [9] . Hence, it is of great importance to explore earth‐abundant transition metal‐based OER electrocatalysts to substitute the precious metal‐based electrocatalysts.…”
Section: Introductionmentioning
confidence: 99%